Osteocalcin, a bone‐derived hormone with important andrological implications. (10th April 2017) - De Toni, L.; Di Nisio, A.; Rocca, M. S.; De Rocco Ponce, M.; Ferlin, A.; Foresta, C.
Summary: Increasing evidence disclosed the existence of a novel multi‐organ endocrine pathway, involving bone, pancreas and testis, of high penetrance in energy metabolism and male fertility. The main mediator of this axis is undercarboxylated osteocalcin (ucOC), a bone‐derived protein‐exerting systemic effects on tissues expressing the metabotropic receptor GPRC6A. The recognized effects of ucOC are the improvement of insulin secretion from the pancreas, the amelioration of systemic insulin sensitivity, in particular in skeletal muscle, and the stimulation of the global endocrine activity of the Leydig cell, including vitamin D 25‐hydroxylation and testosterone production. The supporting evidence of this circuit in both animal and human models is here reviewed, with particular emphasis on the role of ucOC on testis function. The possible pharmacological modulation of this hormonal circuit for therapeutic aims is also discussed.